Conservation of epistemic responsibility by external epistemic in point of view of Ayatollah Javadi Amoli - zeinab askarian; naeime pormohamadi; mohamadmahdi alimardi (حکمت اسرا)
Epistemic duty issue is one of the most important subjects in epistemology. In contrast to the externalism approach, which emphasizes on epistemic duty and responsibility for justification of a belief, the internalism approach regarding epistemology is emerging which focus on the way accepting belief based on cognitive subject rather than epistemic duty. Important issues in this approach are the way of accepting belief and effective factors on the making belief trend. The epistemic value of a belief is determined based on emerging factors. In this approach, providing any justification not necessarily leads to true beliefs eventually finally increasing true beliefs and decreasing false beliefs. Despite in seem that epistemic duty is emerging. Ayatollah Javadi Amoli has an internalism approach and considers that justifications are required to have a belief. On the other hand, as Muslims hakim philosophers does not ignore epistemic process and external effective factors on knowledge. In epistemic process, he considers not epistemic external factor including health of senses, avoiding of sin and access to coaching else.